The dark side of personal response systems (PRSs): Boredom, feedback, perceived learning, learning satisfaction. Issue 7 (3rd October 2021) - Chan, Simon C. H.; Ko, Stephen
Abstract: In the context of the use of personal response systems (PRSs) in the classroom, the two main motivations of the study were to investigate whether boredom with the devices decreased students' perceived learning and learning satisfaction, and whether teachers' provision of feedback moderated these negative effects. A survey was conducted among 172 business undergraduate students at a local university in Hong Kong. Descriptive statistics and regression analyses were used to analyze the data. Results indicated that perceived learning mediated the relationship between boredom and learning satisfaction. This study found that the negative relationship between boredom with PRSs and learning satisfaction was weaker when teachers provided higher levels of feedback. A key managerial implication for academic educators was that teachers could develop better learning experience to students by providing high quality feedback in PRSs context.